Clinical Forms and GRIN2A Genotype of Severe End of Epileptic-Aphasia Spectrum Disorder - Li, Xiao; Xie, Ling-Ling; Han, Wei; Hong, Si-Qi; Ma, Jian-Nan; Wang, Juan; Jiang, Li (Frontiers in Pediatrics, 2020)
Objective To analyze the electroclinical characteristics, gene test results of children on the severe end of the epilepsy aphasia spectrum (EAS), and also the correlation of EAS related GRIN2A genes to explore the genotype-phenotype relationships as well as potential pathogenic mechanism of EAS. Methods A retrospective study was conducted on the participants diagnosed with Landau-Kleffner syndrome (LKS), epileptic encephalopathy with continuous spike-and-wave during sleep (CSWS), and atypical benign partial epilepsy (ABPE) at the Children’s Hospital of Chongqing Medical University from January 2013 to June 2019. Whole-Exome Sequencing was performed in eight patients. In addition, we reviewed all the published literatures reporting EAS patients with pathogenic variants until June 2019, and conducted Gene Ontology (GO) analysis well as Protein-protein interaction (PPI) network. Results The mean age at seizure onset was 55.4±27.0 months. The baseline severity of the spike-wave index (SWI) was not significantly correlated with intellectual disability (ID) level. Two pathogenic de novo GRIN2A null variants were identified in patients with ABPE who had less severe ID, in spite of the electrical status epilepticus during slow-wave sleep (ESES). By literature reviewing, there were 18 GRIN2A missense mutations and 11 GRIN2A truncating mutations which leading to N-methyl-D-aspartate receptors’ loss-of-function has been reported. 9 of them (31.0%) situated in amino (N)-terminal domain ,6 (20.7%) in linger-binding domain S1, and 10 (34.5%) in linger-binding domain S2. EAS related genes were enriched in the biological process of chemical synaptic transmission and vocalization (FDR < 0.01). The hub protein in PPI network is GluN2A, which might affect language function via foxp2-srpx2/uPAR signal network. Conclusion Our data suggested that when children suspected with benign epilepsy of children with centrotemporal spikes (BECTs) have early onset age, changed seizure semiology, and deterioration of behavior/ cognition/ motor function, neurologists should be alert the appearance of ESES. The neuropsychological deterioration in children with EAS might not be completely affected by electric discharge severity, but also genetic etiology. Our finding also enforced the current genotype-phenotype relationship theory about EAS. For EAS children, GRIN2A-FOXP2-SRPX2/uPAR signal network might contribute to the mechanism of their language deficit.